Meranda and the legend of the lake - Mahoney, Meagan (Owlkids Books, 2021)
"11-year-old Meranda thought her life was complicated enough with her weak legs (she needs crutches to walk because of cerebral palsy) and her helicopter parents. She lives in Calgary but has always felt drawn to the East Coast, where her parents grew up...though she's never visited. Her mother, a pediatric ER doctor, has all the excuses: it's too far, it's too expensive, it's not safe near the water. When her great-uncle Mark dies, Meranda's parents finally decide to make the trip-so she gets to stay with her grandparents in their cozy cottage on Bras D'Or Lake. At first, being there is everything she hoped it would be, and she can't get enough of the saltwater smell... or the scrumptious chowder at the local eatery. But soon, secrets begin to unfold: Why does the newspaper headline say her great-uncle Mark's death was suspicious? Why do strangers keep calling Meranda "miracle baby"? Why does her usually calm mother seem so panicky and scared? And what on earth does all this have to do with mermaids?! Meranda and her new friend Claire decide to investigate on their own. But as Meranda begins to sep"--